APPLICATION OF FACTOR ANALYSIS IN EVALUATION OF THE CONSULTING DEVELOPMENT IN SERBIA - Mihailović, Branko; Tepavac, Rajko; S. Kovačević, Maja (Economics of Agriculture, 2012)
The aim of this study is to determine the main factors of development consulting services in Serbia. The verification was done by a procedure, by which have been achieved relevant scientific conclusions – by data research in the field, where had been respected factor analysis criteria, according to which had been possible adequate conclusions and generalization. Namely, taking into consideration the results of empirical research, it can be concluded the following: Three the most important factors of consulting services development are: education and awareness, developmental projects and affirmation of market business. In regard to actual consulting trends in the countries of our region, as well as a level of consulting development in the EU countries, the market of consulting services in Serbia has not developed significantly in last period. The owners and managers of enterprises still do not feel a need for external services, by which they would resolve business problems.